Fatty acid composition, antioxidant and antibacterial activities of Adonis wolgensis L. extract - Maryam Mohadjerani; Rahmatollah Tavakoli; Rahman Hosseinzadeh (Mashhad University of Medical Sciences, 2014)
Objectives: The objective of this study was to analyze the fatty acid content, antioxidant, and antibacterial activities of hydro-methanolic extract of Adonis wolgensis L. (A. wolgensis L.) growing wild in north of Iran. Materials and Methods: Oils of A. wolgensis L. was obtained by means of Soxhlet apparatus from leaves and stems. Methyl esters were derived from the oily mixtures by trans-esterification process and were analyzed by GC/FID and GC/MS systems. Phenolic compounds extraction was done with aqueous methanol (90%). This extract was investigated for antioxidant activity using DPPH radical scavenging and reducing power methods and was also tested against a panel of microorganisms. Results: Linolenic acid (45.83%) and oleic acid (47.54%) were the most abundant fatty acids in leaves and stems, respectively. Hydro-methanolic extract with the high amount of total phenolics (9.20 ±0.011 mg GAE per dry matter) was the potent antioxidant in the assays. Results obtained from measurements of MIC for extract, indicated that E. coli, S. aureus, and S. enteritidis were the most sensitive microorganisms tested, but no activity was observed against Gram-positive microorganism (B. subtilis). Conclusion: The results obtained from the present study indicated that the oil of A. wolgensis leaves and stems contained a high source of poly-unsaturated fatty acids (PUFAs). These results also showed that hydro-methanolic extract of this plant contained significant antioxidant and antibacterial activities.